The Role of Sradha and Bhakti in Efforts to Increase Happiness in the Era of Information Technology - I Putu Putra Astawa; I Made Endra Lesmana Putra; Ni Putu Suwardhani; Ni Nyoman Sri Winarti (PT Inovasi Pratama Internasional, 2023)
Religious values in science or providing religious morality to science. Mastery of science and technology is to improve skills in order to improve the quality of human life, while Sradha and Bhakti (faith and piety) are to increase moral values and wisdom. Therefore, touching on religious values that are based on divine teachings is very important. In this way, the goal of Hindu religious education which is in line with the goals of national education can be achieved, namely developing and increasing Sradha (faith) and Bhakti (devotion) of Hindus towards God Almighty/Ida Sanghyang Widhi Wasa through the appreciation and practice of Hindu religious teachings in order to become Hindu people. who is dharmika and able to realize